The law and economics of privacy, personal data, artificial intelligence, and incomplete Mmonitoring - Langenfeld, James; Fagan, Frank; Clark, Samuel (Data scientist) (Research in law and economics, 2022)
"The Law and Economics of Privacy, Personal Data, Artificial Intelligence, and Incomplete Monitoring presents new findings and perspectives from leading international scholars on several emerging areas issues in legal and economic research. The collection contains new theoretical papers on privacy, the protection of personal data, the use of regulatory monitoring under legal standards versus rules, a study of the properties of market efficiency in securities fraud litigation, as well as an analysis of non-exclusionary price floors. It also contains an empirical paper on the relationship between uncertainty of patent approval of artificial intelligence applications and the Supreme Court's decision in Alice Corp. v. CLS Bank International. Finally, the volume features a law-and-economics assessment of the Chinese financial system within the context of the trade-off between centralized control and rapid growth. This 30th volume of Research in Law and Economics showcases the cutting edge theoretical and empirical findings for researchers and professionals considering these complex issues intersecting law, technology, and economics."--Publisher's description.